CHILDREN SONGS AND DANCES (BASSARI, BÉDIK & MALINKE) FROM SENEGAL, AFRICA KÉDOUGOU (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This presentation attempts to show how the fields of pedagogy and research not only share spaces but also exchange tools and logic. This experimental project enables a role reversal among those involved; in this case, a group of Senegalese teachers and students seeking to recover their respective children’s musical heritage. At a certain point, it is the student who teaches and informs the teacher, and both participate actively and autonomously in the recovery of their own repertoires; a way of emancipating Africans from Westerners in the study of their own music.
Keywords: Kédougou (Senegal), Research-Pedagogy, Children’s music, Role reversal, Musical heritage recovery.